FDG PET/CT Findings in Abdominal Fat Necrosis After Treatment for Lymphoma. (May 2016) - Dubreuil, Julien; Moreau, Aurélie; Sarkozy, Clémentine; Traverse-Glehen, Alexandra; Skanjeti, Andrea; Salles, Gilles; Giammarile, Francesco
Abstract : Abstract: FDG PET/CT is now validated in non-Hodgkin lymphoma for response assessment in interim and posttreatment lymphoma. We report the case of a 62-year-old man followed by FDG PET/CT for a diffuse large B-cell lymphoma, with initial stage III. The interim FDG PET/CT examination concluded in complete metabolic and morphological response of subdiaphragmatic lymphadenopathy but a persistent abnormal subdiaphragmatic uptake (SUVmax at 9 and Deauville 5-point scale at 5). Therefore, an abdominal biopsy of the corresponding nodules was conducted with a final diagnosis of diffuse fat necrosis.